2014
DOI: 10.1080/03067319.2014.974588
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds, antioxidant activity and Cu, Zn, Cd and Pb content in wild and cultivated cranberries and blueberries

Abstract: The aim of this study was to determine the content of Cu, Zn, Cd and Pb and the total polyphenol (TP) content as well as the total antioxidant capacity (TAC) in wild cranberries and blueberries collected from different localities of the Slovakia and to compare them with properties of six cranberry and six highbush blueberry cultivars obtained from the research centre. Compared with cultivated cranberries (Cu, Zn, Cd and Pb content: 0.642, 1.496, 0.015 and 0.050 mg/kg FM) in wild fruits, higher Cu (by 37%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The water extracts of berries are important from the household brewing and consumption [ 20 – 22 ]. For incorporation into a functional beverage, aqueous alcohol have been used with the aim to maximizing the active ingredients [ 23 25 ]. As previously observed [ 26 , 27 ], an increase in the extraction temperature can promote higher phenolics solubility from plant materials, but also heat treatment may be responsible for their partial destruction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The water extracts of berries are important from the household brewing and consumption [ 20 – 22 ]. For incorporation into a functional beverage, aqueous alcohol have been used with the aim to maximizing the active ingredients [ 23 25 ]. As previously observed [ 26 , 27 ], an increase in the extraction temperature can promote higher phenolics solubility from plant materials, but also heat treatment may be responsible for their partial destruction.…”
Section: Resultsmentioning
confidence: 99%
“…Significantly lower results (0.36–0.41 mg GAE/g) for various lingonberry extracts (methanol, ethanol, acetone, ethyl acetate and their mixture with water) were reported for fruits harvested from southern Labrador area in Canada [ 31 ]. The average total polyphenol content determined in wild blueberries collected from different localities in Slovakia was 2.86 mg GAE/g and it was 97% higher compared to highbush cultivars (1.45 mg GAE/g) [ 23 ]. The variation between the results presented in this paper and the previously published data can be explained by the influence of cultivar, ripening stage, weather and soil conditions as well as various applied extraction methods.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, none of these berries would represent a risk to human health from this point of view. Vollmannova et al [ 11 ] found higher Cu, Zn, and Pb and similar Cd contents in wild blueberries collected in Slovakia in comparison with highbush blueberry cultivar; however, the soil content where the fruits were grown was not examined.…”
Section: Resultsmentioning
confidence: 99%
“…The content of anthocyanins and other phenolic compounds in different species of blueberry (wild and cultivated) are quite often determined and compared [ 6 10 ]. Concentration of essential elements, which are also the important components of blueberry fruits, was rarely reported [ 11 , 12 ]. Trace elements play an important role in the functioning of the human body.…”
Section: Introductionmentioning
confidence: 99%
“…However, in another study, the antioxidant capacities of fruits of wild and cultivated cranberries were similar, without a statistically significant difference ( p < 0.05) [ 70 ]. Furthermore, wild cranberries exhibited a lower average antioxidant capacity than cultivated berries [ 71 ]. Similarly, hydroalcoholic extracts of wild murtilla ( Ugni molinae ) fruit showed weaker DPPH· and ABTS· scavenging capacity than cultivated ones [ 72 ].…”
Section: Bioactivities Of Wild Fruitsmentioning
confidence: 99%